Long Non-coding RNAs and Circular RNAs: Insights Into Microglia and Astrocyte Mediated Neurological Diseases - Chen, Miaomiao; Lai, Xingning; Wang, Xifeng; Ying, Jun; Zhang, Lieliang; Zhou, Bin; Liu, Xing; Zhang, Jing; Wei, Gen; Hua, Fuzhou (Frontiers in Molecular Neuroscience, 2021)
Microglia and astrocytes maintain tissue homeostasis in the nervous system. Both microglia and astrocytes have pro-inflammatory phenotype and anti-inflammatory phenotype. Activated microglia and activated astrocytes can contribute to several neurological diseases. Long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs), two groups of non-coding RNAs (ncRNAs), can function as competing endogenous RNAs (ceRNAs) to impair the microRNA (miRNA) inhibition on targeted messenger RNAs (mRNAs). LncRNAs and circRNAs are involved in various neurological disorders. In this review, we summarized that lncRNAs and circRNAs participate in microglia dysfunction, astrocyte dysfunction, neuron damage, and inflammation. Thereby, lncRNAs and circRNAs can positively or negatively regulate neurological diseases, including spinal cord injury (SCI), traumatic brain injury (TBI), ischemia-reperfusion injury (IRI), stroke, neuropathic pain, epilepsy, Parkinson’s disease (PD), multiple sclerosis (MS), and Alzheimer's disease (AD). Besides, we also found a lncRNA/circRNA-miRNA-mRNA regulatory network in microglia and astrocyte mediated neurological diseases. Through this review, we hope to cast light on the regulatory mechanisms of lncRNAs and circRNAs in microglia and astrocyte mediated neurological diseases and provide new insights for neurological disease treatment.